2013
DOI: 10.1037/a0027947
|View full text |Cite
|
Sign up to set email alerts
|

Improving the past and the future: A temporal asymmetry in hypothetical thinking.

Abstract: Current views of hypothetical thinking implicitly assume that the content of imaginary thoughts about the past and future should be the same. Two experiments show that, given the same experienced facts of reality, future imagination may differ from past reconstruction. When participants failed a task, their counterfactual thoughts focused on uncontrollable features of their attempt (e.g., "Things would have been better if the allocated time were longer/if I had better logic skills"). But their prefactual thoug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
58
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(71 citation statements)
references
References 28 publications
12
58
0
1
Order By: Relevance
“…These results replicate the results obtained when participants reflected on their failures in Ferrante et al (2013), and extend them to situations in which participants reflect on their successes. In both cases, participants tend to produce more uncontrol-2 The minor difference in the framing of the counterfactual and prefactual question could have focused the prefactual question ("things will be better for me in the next game if") more on the task and the counterfactual question ("things would have been better for me if") more on the participant's experience.…”
Section: Resultssupporting
confidence: 78%
See 3 more Smart Citations
“…These results replicate the results obtained when participants reflected on their failures in Ferrante et al (2013), and extend them to situations in which participants reflect on their successes. In both cases, participants tend to produce more uncontrol-2 The minor difference in the framing of the counterfactual and prefactual question could have focused the prefactual question ("things will be better for me in the next game if") more on the task and the counterfactual question ("things would have been better for me if") more on the participant's experience.…”
Section: Resultssupporting
confidence: 78%
“…These results confirm and extend those obtained in earlier studies (e.g., Ferrante et al, 2013;Girotto et al, 2007;Pighin et al, 2011), and conflict with the predictions of the preparatory hypothesis (e.g., Epstude & Roese, 2008Markman et al, 1993, Roese, 1997. If counterfactuals mainly serve to prepare future performance, they should be of the controllable sort, they should not differ from prefactuals, and they should not be affected by external prompts.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…However, learning from past mistakes or and improving future performance can only be achieved if people focus on things they can change in the future (i.e., controllable aspects of the event or behaviour). Just generating counterfactual thoughts may not be sufficient in and of itself to benefit individuals and recent research found that people were more likely to generate controllable thoughts when thinking hypothetically about the future (prefactual thinking) than when thinking hypothetically about the past (counterfactual thinking) (Ferrante, Girotto, Straga, & Walsh, 2013). It may be the case that prefactual thoughts are more functional than counterfactual thoughts, although individual differences may play a role in modifying the functionally of counterfactual thoughts.…”
Section: The Effect Of Controllability and Causality On Counterfactuamentioning
confidence: 87%